Norms of Interocular Circumpapillary Retinal Nerve Fiber Layer Thickness Differences at 768 Retinal Locations - Baniasadi, Neda; Rauscher, Franziska; Li, Dian; Wang, Mengyu; Choi, Eun Young; Wang, Hui; Peschel, Thomas; Wirkner, Kerstin; Kirsten, Toralf; Thiery, Joachim; Engel, Christoph; Löffler, Markus; et al. (Translational Vision Science & Technology, 2020)
Purpose: The onset and progression of optic neuropathies like glaucoma often occurs asymmetrically between the two eyes of a patient. Interocular circumpapillary retinal nerve fiber layer thickness (cpRNFLT) differences could detect disease earlier. To apply such differences diagnostically, detailed location specific norms are necessary.